2019
DOI: 10.3892/mmr.2019.10603
|View full text |Cite
|
Sign up to set email alerts
|

Increased lncRNA HOTAIR expression promotes the chemoresistance of multiple myeloma to dexamethasone by regulating cell viability and apoptosis by mediating the JAK2/STAT3 signaling pathway

Abstract: Multiple studies have shown that HoX antisense intergenic rna (HoTair), an oncogenic long non-coding rna (lncrna), is dysregulated in leukemia and is involved in tumor progression. The aim of the present study was to determine whether HoTair could serve as a novel biomarker for the diagnosis of multiple myeloma (MM), and to investigate its role in regards to MM cell viability and chemoresistance to dexamethasone (deX). The results revealed that the expression of HOTAIR was significantly upregulated in serum, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…A single lncRNA can act via multiple signaling pathways. For example, lncRNA HOTAIR acts through miR-204-5p/HMGB1 axis [ 40 ], miR-519a-3p/RRM1 axis [ 41 ], miR-601/ZEB1 axis [ 42 ], JAK2/STAT3 [ 43 ], hexokinase-2 [ 44 ], PI3K/Akt/mTOR [ 45 ] among other pathways. PlncRNA-1, is a newly identified lncRNA located on human chromosome 21 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single lncRNA can act via multiple signaling pathways. For example, lncRNA HOTAIR acts through miR-204-5p/HMGB1 axis [ 40 ], miR-519a-3p/RRM1 axis [ 41 ], miR-601/ZEB1 axis [ 42 ], JAK2/STAT3 [ 43 ], hexokinase-2 [ 44 ], PI3K/Akt/mTOR [ 45 ] among other pathways. PlncRNA-1, is a newly identified lncRNA located on human chromosome 21 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the lncRNA, TUG1, contributes to the proliferation and migration of hepatocellular carcinoma cells in vivo by upregulating miR-144 via inactivation of the JAK2/ STAT3 pathway (35). Moreover, the lncRNA, HOTAIR, was found to promote multiple myeloma cell viability and increase chemoresistance to dexamethasone via the JAK2/ STAT3 signaling pathway (36). We are of the opinion that KCNQ1OT1 competitively binds to microRNAs and regulates the downstream oncogenes or signaling pathways.…”
Section: Discussionmentioning
confidence: 95%
“…lncRNAs also can promote chemoresistance by regulating tumor cells' apoptosis and cell cycle. Guan et al have revealed that elevated levels of the lncRNA HOTAIR increase the chemoresistance of MM to dexamethasone by regulating apoptosis and cell viability by downregulating the JAK2/STAT3 signaling pathway in peripheral blood, bone marrow samples, and MM cell lines [164]. Similarly, HCC cells that are resistant to chemotherapy drugs, such as docetaxel, 5-FU, and mitomycin, have higher levels of MALAT1 expression.…”
Section: The Role Of Lncrnas In Cancer Therapy Resistancementioning
confidence: 99%